The Effect of Green Accounting and Environmental Awareness on Environmental Performance in Manufacturing Companies in Indonesia - Ni Made Lily Trisna DEWI; Ni Komang Purnama DEWI; Ni Kadek Dian Setya WARDANI; Anak Agung Istri Intan Pradnya PUTRI; Desak Nyoman WULANDARI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:Increasing awareness of sustainability is driving manufacturing companies in Indonesia to be more responsible for their environmental impact. Green accounting is one of the modern accounting approaches that incorporates environmental costs into the company's reporting system, while environmental awareness reflects the awareness of management and employees in maintaining environmental sustainability.Methodology:This study uses a literature review method on various relevant national and international journals in order to analyze the relationship between the two variables and environmental performance.Findings:The results of the study show that manufacturing companies that actively implement green accounting tend to have more efficient waste management and energy consumption, and are more compliant with environmental regulations. On the other hand, environmental awareness has been shown to encourage more environmentally conscious managerial actions, as well as strengthen the effectiveness of the implementation of green accounting itself. The combination of a structured environmental reporting system and internal organizational awareness has been shown to improve environmental performance significantly.Implication:The implications of these findings emphasize the importance of integration between technical and value approaches in the sustainability management of the manufacturing industry.